Reach and perceived effectiveness of a community-led active outreach postvention intervention for people bereaved by suicide - Hill, Nicole T. M.; Walker, Roz; Andriessen, Karl; Bouras, Hamza; Tan, Shawn R.; Amaratia, Punam; Woolard, Alix; Strauss, Penelope; Perry, Yael; Lin, Ashleigh (Frontiers in Public Health, 2022)
Background: Postvention is a core component of suicide prevention strategies, internationally. However, the types of supports provided to people impacted by suicide vary widely. This study examines the perceived effectiveness of the Primary Care Navigator (PCN) model for people bereaved by suicide. The PCN model was implemented in response to a suicide cluster. It is an active outreach postvention intervention, initiated by police in response to a suspected suicide and links individuals to support in the immediate aftermath of their loss. Methods: A retrospective cross-sectional mixed methods approach was used to (1) identify the reach of the PCN model, (2) describe the type of support provided to people bereaved by a suspected suicide and (3) identify the perceived effectiveness of the PCN model from the perspective of WA police, postvention stakeholders and individuals bereaved by suicide. Quantitative data was used to examine the characteristics of suicide in the region, the characteristics of people who received bereavement support, and the types of support that were provided. Interviews with police, postvention stakeholders, and people bereaved by a suspected suicide were conducted to identify the perceived effectiveness of the intervention. Results: Between 1 January 2019 to 31 March 2021 there were 80 suspected suicides. Active outreach was provided to 347 bereaved individuals via the PCN model. Just under half of those who were offered outreach accepted further support (n=164) in the form of suicide bereavement information (98%), mental health or clinical support (49.6%), specialised postvention counselling (38.4%), financial assistance (16%) and assistance with meals (16%), followed by housing assistance (14%) and referral to community services (11%). Police, stakeholders, and people with lived experience of a suspected suicide perceived the PCN model to be effective at connecting them to the community, linking people to support, and preventing suicide. Conclusion: The results provide evidence supporting the perceived effectiveness of an active outreach approach to postvention that provides acute support to people bereaved by suicide. Findings highlight important practical areas of support such as providing referral pathways and information on grief and suicide loss in the immediate aftermath of a suicide loss.